Destino e gestão aos resíduos de lâmpadas elétricas a descarga - Junior, Elvo C. Burini (2012)
The use of gas discharge lamps is an important instrument to reduce energy demand and to increase efficiency at the end use of energy. It has been considered under the electrical energy reduction purposes. In this work the environment point of view was aggregated. After the bulb life time end the final destination of the harmful elements contained in it must be treated with focus on management of hazardous waste. Large data variability on the amount of Mercury (Hg) detected inside the discharge tube of the lamps were observed, particularly at fluorescent bulbs. The current situation in Brazil, where electricity generation is not based on burning coal and a greater market diffusion of bulbs based on Hg technology can induce increase in the emission of Hg during the bulb life cycle, unlike at the U.S. and other countries. Investments for the main equipments to quantify Hg content in discharge tubes from lamps were discussed and estimated.